2019
DOI: 10.1029/2018jg004809
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Precipitation on Mercury Accumulation on Subtropical Montane Forest Floor: Implications on Climate Forcing

Abstract: Processes facilitated by precipitation play an important role on mercury (Hg) accumulation on forest floor and therefore key to Hg cycling in forest ecosystems. Sites along the windward slope of 1,250 to 2,400 m at Mt. Ailao, Southwestern China, have higher precipitation than the leeward slope sites. In this study, measurements of Hg concentration and associated stable isotope composition for soil, fresh, and degraded litterfall samples were made at sites along two slopes of Mt. Ailao to quantify the direct an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 95 publications
(152 reference statements)
3
26
1
Order By: Relevance
“…The soil Hg concentrations in Oe (underlain by a partially decomposed layer) and Oa (a very dark layer of well-decomposed humus) are higher than those in Oi (litter and twigs) at Hailuogou, which can be attributed to the greater litter mass loss during the initial litter decomposition, leading to Hg accumulation in Oe and Oa. This is consistent with earlier studies showing Hg concentration changes during litter decomposition (16,17) and also supported by the increase in the Hg/C ratio from Oi to Oa (SI Appendix, Fig. S5).…”
Section: Significancesupporting
confidence: 93%
See 1 more Smart Citation
“…The soil Hg concentrations in Oe (underlain by a partially decomposed layer) and Oa (a very dark layer of well-decomposed humus) are higher than those in Oi (litter and twigs) at Hailuogou, which can be attributed to the greater litter mass loss during the initial litter decomposition, leading to Hg accumulation in Oe and Oa. This is consistent with earlier studies showing Hg concentration changes during litter decomposition (16,17) and also supported by the increase in the Hg/C ratio from Oi to Oa (SI Appendix, Fig. S5).…”
Section: Significancesupporting
confidence: 93%
“…Overall, we found that soil Hg originated primarily from atmospheric sources at Hailuogou and from geological sources at Midui. This is also supported by a significant positive correlation (r = 0.8235, P < 0.001, n = 93) between the content of soil organic carbon (SOC), which can serve as a surrogate for plant productivity in glacier-retreated regions (4,17), and the fraction of atmospheric Hg 0 in soil. Higher plant productivity at Hailuogou thus induces greater atmospheric Hg 0 accumulation than at Mingyong and Midui.…”
Section: Significancementioning
confidence: 82%
“…In the SMD forest, it ranges from 0.5 ± 0.2 μg m −2 month −1 to 4.8 ± 3.5 μg m −2 month −1 , with an overall mean monthly deposition of 1.6 ± 0.9 μg m −2 month −1 (Figures 2a and 2b). These values are 30%-40% lower than those reported in our earlier studies (Wang, Yuan, Lu, et al, 2019;, because the litterfall refers mainly to the leaf litterfall in this study, but includes all the litterfall in our earlier studies. The r value between litterfall Hg deposition and litterfall biomass production is up to 0.99, much higher than that (0.26) between litterfall Hg deposition and litterfall Hg concentration (Figure 3a).…”
Section: Impacts From Extreme Weather On Litterfall Hgcontrasting
confidence: 73%
“…For forest soil sampling, six replicates of 10 m × 10 m subplots were established at each site (Z. Y. Lu et al., 2016; Wang, Lin, Lu, et al., 2016; Wang, Yuan, Lu, et al., 2019). We mainly collected forest humus soils (3–5 cm depth from the forest floor; reflecting short‐term (decadal) variations and top mineral soils (0–20 cm; reflecting long‐term [hundreds of years]) variations in this study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation